Low loss and omnidirectional Si3N4 waveguide for label-free spatial frequency shift super-resolution imaging. (24th May 2021) - Ye, Dehao; Tang, Mingwei; Liu, Xiaowei; Ma, Yaoguang; Liu, Xu; Yang, Qing
Abstract: Waveguide-based spatial frequency shift (SFS) super-resolution imaging has attracted growing interest for its high integration, low cost and compatibility with integrated circuit processes. However, a missing band in the spatial frequency (SF) domain severely impedes the final distortionless super-resolution image reconstruction. Here, we present a tunable multi-wavelength SFS method that can light the sample with tunable wavelength illuminations in a sequence using multiple directions of waveguide illumination. The SFS scheme provides broad and complete spectrum information, enabling a reconstructed super-resolution image with high fidelity. An etched three-slot structure and randomly distributed polymer beads on the waveguide surface are imaged and reconstructed with a Gerchberg–Saxton (G-S) SF synthesis algorithm. To the best of our knowledge, this is the first report that shows the waveguide-based label-free super-resolution imaging capability of complex random samples. In the future, the novel SFS imaging waveguide can potentially be integrated with conventional microscopes for chip-based label-free super-resolution imaging.